Privilégio branco e a (im)possibilidade de implementação de políticas antirracistas: o caso do Instituto Federal de Educação, Ciência e Tecnologia de Mato Grosso - Arruda, Maria Auxiliadora de Almeida (2020)
Racism and racial discrimination are constitutive of Brazilian education, practices and social relations. A Whiteness refers to the way in which isolated whites are appropriate for the category race and racism in the constitution of their subjectivities and when appropriate that “being whitw” determines the moral, intellectual and aesthetic characteristics of individuals that differentiate others. Thus, the objective of this research was to understand the process of reserving vacancies for the integrated medium level of professional training, implemented in the period 2008-2018 by the Federal Institute of Education, Science and Technology of Mato Grosso - IFMT, created by Law 11.892 / 2008 and currently consists of 19 campuses distributed in all mesoregions of MT, predominantly in the northern Mato Grosso mesoregion, where there is a higher proportion of white population and intensive agricultural productionº The IFMT offers vocational education at all levels and modalities aimed at the local market, and is also a limited reserve of quality public education in MT, especially in the provision of integrated secondary education to vocational training. The research was conducted at IFMT- Campus Cuiabá, in a qualitative approach in which the methods used for data generation were: document analysis, interviews with servers and students and observationº It is concluded that the IFMT vacancy reservation process allowed unequal opportunities for whites and blacks and there were ostensibly privileges for the white group, since in the period 2009-2012 it used only the socioeconomic and non-racial criteria. And from 2012 onwards it showed a particularity: the racial criterion was included using official and local or native classification categories called “other ethnicities”, which in turn was replaced in 2017 by the term non-self-declaration of color / race and from 2018 shifted to the public school and income criteria. This category reflects the local social imaginary of the existence of an ethnic and or racial democracy and a racially homogeneous and harmonious state marked by the class and non-racial problem. Thus, the 2012-2018 IFMT vacancy reservation policy maintained a very ambivalent relationship close to the meanings of whiteness, namely: racial neutrality, praise for miscegenation, omission of racial inequality and discrimination, silence around racial issues supported by the strategy of subsuming race in the class and category of other ethnic groups and in the eminently redistributive, meritocratic and fallacious discourse of racial equality. This policy operates in the IFMT - Cuiabá campus school context as a difference marker that hierarchizes and divides students and positions black students in less prestigious courses and classes considered to have less cognitive development.